Estrategias didácticas para la lectura comprensiva en los estudiantes del sexto grado de la escuela de Educación General Básica "Luz de América" durante el período lectivo 2020-2021- - Grijalba Salazar, Nancy Elizabeth (2021)
This research was framed in "Didactic Strategies for Comprehensive Reading" which constitutes the object of research and is determined as a field of action to reading comprehension linked to Basic Education sub-level, for which it was proposed as a general objective: Strengthen the process of reading comprehension through didactic strategies in sixth grade students of the School of Basic General Education "Luz de América". The research project was focused on the quantitative and qualitative. The execution of the project was feasible because it had bibliographic information taken from several previous works, the diagnosis was made and its application in the place under investigation because the problem statement describes the need for students to improve the development of Comprehensive reading through didactic strategies through a proposal focused on a specific objective. This led to the design of a manual of didactic strategies for comprehensive reading in sixth grade students, which was socialized with teachers who work in the Education sub-level and applied with sixth grade students of Parallel “A” Basic Education. It was validated by the criteria of experts with experience in the educational field, finally it was applied as an alternative solution to the development of comprehensive reading and with its application an improvement was evidenced in students by understanding more easily what they read and the different texts they read. is presented to them.